Singapore Chinese Eye Study: key findings from baseline examination and the rationale, methodology of the 6-year follow-up series - Majithia, Shivani; Tham, Yih Chung; Chee, Miao Li; Teo, Cong Ling; Chee, Miao-Ling; Dai, Wei; Kumari, Neelam; Lamoureux, Ecosse Luc; Sabanayagam, Charumathi; Wong, Tien Yin; Cheng, Ching-Yu (British journal of ophthalmology, 2020)
Background/aimsIn order to address the eye care needs of the increasing numbers of elderly Chinese globally, there is a need for comprehensive understanding on the longitudinal trends of age-related eye diseases among Chinese. We herein report the key findings from the baseline Singapore Chinese Eye Study (SCES-1), and describe the rationale and methodology of the 6-year follow-up study (SCES-2).Methods3353 Chinese adults who participated in the baseline SCES-1 (2009–2011) were invited for the 6-year follow-up SCES-2 (2015–2017). Examination procedures for SCES-2 included standardised ocular, systemic examinations and questionnaires identical to SCES-1. SCES-2 further included new examinations such as optical coherence tomography angiography, and questionnaires to evaluate health impact and economic burden of eye diseases.ResultsIn SCES-1, the age-adjusted prevalence of best-corrected low vision (VA<6/12, better-seeing eye) and blindness (VA<6/60, better-seeing eye) were 3.4% and 0.2%, respectively. The prevalence rates for glaucoma, age related macular degeneration, and diabetic retinopathy (among diabetics) were 3.2%, 6.8%, 26.2%, respectively. Of the 3033 eligible individuals from SCES-1, 2661 participated in SCES-2 (response rate=87.7%). Comparing with those who did not attend SCES-2, those attended were younger, had higher SES (all p<0.001), but less likely to be a current smoker, to have diabetes, hypertension, hyperlipidaemia (all p≤0.025).ConclusionsBuilding on SCES-1, SCES-2 will be one of the few longitudinal population-based eye studies to report incidence, progression, and risk factors of major age-related eye diseases. Findings from this cohort may offer new insights, and provide useful reference information for other Chinese populations elsewhere.